Pengaruh sensory experience, emotional experience dan social experience terhadap customer satisfaction pada layanan pengemudi ojol perempuan di Prigen - Sri Suprapti; Yurilla Endah Muliatie; Rena Febrita Sarie; Nur Jannah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
With this research, it is hoped that empirical evidence will be obtained regarding the influence of Sensory Experience, Emotional Experience, Social Experience on Customer Satisfaction in the service of female ojol drivers in Prigen. Respondents in this study were online-based transportation customers who used the services of 40 female ojol examiners. Purposive Sampling method was used for sampling, namely respondents with the criteria of having purchased using female motorcycle taxi services at least 1 time and the Convinience Sampling method were respondents who were asked to fill out a questionnaire based on the ease of being found and the time allowance they had. It can be concluded in this study that Sensory Experience, Emotional Experience and Social Experience have a significant effect on Customer Satisfaction in the service of female ojol drivers in Prigen. The variable that has the dominant influence is the Social Experience variable.